THE EFFECT OF PERSONALIZED BACKGROUND MUSIC ON THE STUDENTS' NEUROCOGNITIVE IN READING COMPREHENSION - Nurmutmainna; Eny Syatriana; Junaid (Indonesian Journal of Psycholinguistics, 2022)
This study aimed to improving students' reading comprehension skills by measuring and knowing the achievement of the students neurocognitive in reading comprehension through personalized background music. This research utilized a pre-experimental research method with a quantitative approach which involved all of the second grade students at SMPN 2 Aralle as the sample of this research. This research instrument is a reading text containing 10 number of essay test. The research result shows an improvement on the students’ neurocognitive in reading comprehension after doing the treatment with personalized background music in learning process. It proved the post-test mean score was more significant than the pre-test (72.22%>53.89%). The result of the research was effective in improving students reading comprehension.